﻿Pharmacological correction of the sequelae of acute alcohol-induced myocardial damage with new derivatives of neuroactive amino acids coupled with the blockade of the neuronal NO synthase isoform - Margarita V. Kustova; Valentina N. Perfilova; Igor I. Prokofiev; Elena A. Musyko; Aida S. Kucheryavenko; Elena E. Kusnetsova; Diana E. Tsetsera; Ivan N. Tyurenkov (Belgorod National Research University, 2022)
Introduction: Acute alcohol intoxication (AAI) induces a number of myocardial disorders, which result in mitochondrial dysfunction in cardiomyocytes, oxidative stress, and decreased cardiac contractility. Nitric oxide produced by the nNOS is one of the major modulators of cardiac activity. New derivatives of GABA (RSPU-260 compound) and glutamate (glufimet) can be potentially regarded as such agents as the interaction between the NO system and the GABA and glutamatergic systems has been proved. Materials and methods: All the studies were performed on female white Wistar rats, aged 10 months, whose weight was 280-320g AAI intoxication was modeled of 32% ethanol (gavage, 4g/kg). Results and discussion: Glufimet and the RSPU-260 compound caused a significant improvement in myocardial contractility, increased oxygen consumption in the V3 state according to Chance, raised the respiratory control ratio and decreased the intensity of LPO intensity. Their effectiveness exceeded that of mildronate, their comparator. nNOS inhibition resulted in a pronounced aggravation of oxidative stress implicated in MDA accumulation in cardiac mitochondria and decreased activity of SOD; myocardial contractility and mitochondrial function indicators did not show a significant difference from the control group. The compounds under study coupled with nNOS inhibition had a cardioprotective effect. Conclusion: Glufimet and the RSPU-260 compound, derivatives of neuroactive amino acids, have a pronounced cardioprotective effect, restrict LPO processes, enhance SOD activity, improve the mitochondrial respiratory function after acute alcohol intoxication when coupled with neuronal NO-synthase inhibition, the expression of which persists after AAI. Graphical abstract: